2008
DOI: 10.1007/s10529-008-9786-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute responses of mice livers to short-term exposure to nano-sized or micro-sized silver particles

Abstract: Mice were fed either 13 nm silver nanoparticles or 2-3.5 mum silver microparticles. The livers were then obtained after 3 days and subjected to a histopathological analysis. The nanoparticle-fed and microparticle-fed livers both exhibited lymphocyte infiltration in the histopathological analysis, suggesting the induction of inflammation. In vitro, a human hepatoma cell line (Huh-7) was treated with the same silver nanoparticles and microparticles. The mitochondrial activity and glutathione production were hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(86 citation statements)
references
References 19 publications
4
78
2
2
Order By: Relevance
“…Several animal studies have reported that dietary intake of silver nanoparticles caused lymphocyte infiltration, pigmentation of villi, discharge of mucus granules, and an abnormal mucus composition in the intestine. [21][22][23][24] Animal studies have reported that silver nanoparticles can accumulate in various organs after ingestion, including the liver, kidneys, spleen, stomach, and small intestine. 15,25,26 These results suggest that silver nanoparticles can be absorbed by the GIT into the systemic circulation, and then be distributed throughout various organs.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Several animal studies have reported that dietary intake of silver nanoparticles caused lymphocyte infiltration, pigmentation of villi, discharge of mucus granules, and an abnormal mucus composition in the intestine. [21][22][23][24] Animal studies have reported that silver nanoparticles can accumulate in various organs after ingestion, including the liver, kidneys, spleen, stomach, and small intestine. 15,25,26 These results suggest that silver nanoparticles can be absorbed by the GIT into the systemic circulation, and then be distributed throughout various organs.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Due to its antimicrobial properties, it is used in many domains including medicine (Dongwei et al, 2009). However, silver ion (Ag + ) is cytotoxic (Cha et al, 2008) and its utilization as a feed additive requires a chelation consisting in reducing positive charge (Ag + ) to non charge (Ag 0 ) molecule.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 AgNPs were found in various body tissues, including the blood, brain, liver, spleen, kidneys, thymus, lungs, and heart. [14][15][16][17][18][19] Previous studies have demonstrated that AgNPs can exert cytotoxic and genotoxic effects both in vitro (human cell lines [20][21][22][23][24][25] ) and in vivo (mice 26,17 and fish 27,28 ). Oxidative stress can strongly affect testicular functions important for spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%